2011
DOI: 10.1074/jbc.m110.200584
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Rotation of the Cyanobacterial F1-ATPase Containing Thiol Regulation Switch

Abstract: F 1 -ATP synthase (F 1 -ATPase) is equipped with a special mechanism that prevents the wasteful reverse reaction, ATP hydrolysis, when there is insufficient proton motive force to drive ATP synthesis. Chloroplast F 1 -ATPase is subject to redox regulation, whereby ATP hydrolysis activity is regulated by formation and reduction of the disulfide bond located on the ␥ subunit. To understand the molecular mechanism of this redox regulation, we constructed a chimeric F 1 complex (␣ 3 ␤ 3 ␥ redox ) using cyanobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…On this point, further analysis is required to understand how the conformational change caused by redox regulation is transferred to the catalytic site(s) in CF 1 enzyme molecule. Previously, we constructed a chimeric cyanobacterial F 1 complex in which the 9-amino acid region of spinach CF 1 -␥ including two regulatory Cys was introduced into the cyanobacterial ␥ subunit (36). Based on the single molecular observation of rotation of this chimeric complex, we concluded that redox regulation is achieved by controlling the probability to lapse into ADP inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this point, further analysis is required to understand how the conformational change caused by redox regulation is transferred to the catalytic site(s) in CF 1 enzyme molecule. Previously, we constructed a chimeric cyanobacterial F 1 complex in which the 9-amino acid region of spinach CF 1 -␥ including two regulatory Cys was introduced into the cyanobacterial ␥ subunit (36). Based on the single molecular observation of rotation of this chimeric complex, we concluded that redox regulation is achieved by controlling the probability to lapse into ADP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the major mechanism that acts to regulate its activity is ADP inhibition of the catalytic sites (11,12,14,42), the reason that sites of redox regulation and the ⑀ inhibition are structurally distant from the catalytic site is poorly understood. We postulated that the relative slippage of the two central ␣-helices of the ␥ subunit, which connect the two active domains for catalysis and regulation in the structure of the complex (8), must be a main cause of the change in the enzyme activity (36). To examine this hypothesis, we prepared several mutant complexes in which the relative slippage of two central ␣-helices can be locked at a certain position by disulfide bond formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be related to the fact that both ␥ and ⑀ subunits play critical roles in regulation of the activity of the enzyme (5,6). In comparison with bacterial or mitochondrial ATPases, the chloroplast F 1 (CF 1 ) ␥ subunit contains an additional inserted region of ϳ35 residues, within which two cysteine residues allow redox regulation of ATPase activity by disulfide bond formation/elimination (7)(8)(9)(10). Notably, though containing a similar insertion, the ␥ subunit of cyanobacterial F 1 lacks nine amino acids therein, including the two regulatory cysteines (11).…”
mentioning
confidence: 99%
“…Cyanobacteria do not possess regulatory cysteines in their γ-subunits, although a similar γ-insertion can be found [20,25]. However, the regulation mechanism found in CF 1 was successfully transferred to a cyanobacterial enzyme by insertion of the cysteine-containing fragment from spinach CF 1 into the globular domain of the prokaryotic γ-subunit [26]. A major benefit of studying the ATPase redox regulation is the preservation of crucial interactions between the γ-stalk and the α 3 β 3 hexamer, despite the insertion.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 94%